Creation of Gold Nanoparticles with the Use of Nigella sativa L. Plant Extract Derived from Agricultural Waste Components and Its Potential as a Biomedical Agent - Mehmet Fırat Baran (Journal of Agricultural Sciences)
In this study, gold nanoparticles were rapidly synthesized with a low-cost and environmentally friendly approach through the extract prepared using agricultural waste parts of the Nigella sativa L. plant. Properties of gold nanoparticles from N. sativa leaf extract UV-visible Spectrophotometer, X-ray diffraction, Electron Disperse X-ray, Zeta potential and Zetasizer, Field Emission Scan Electron Microscopy (FESEM), Atomic Power Microscopy, Transmission Electron Microscopy (TEM), thermogravimetric and differential thermal analysis characterized by its data. It was observed that the morphologies of the synthesized gold nanoparticles (AuNPs) exhibited a spherical appearance with an average size distribution of 107 nm and a monodisperse. In addition, they were found to be stable structures at -17.7 mV surface charge, and maximum absorbance at 538.41 nm. For the usability of AuNPs as biomedical agents, antimicrobial and anticancer effects were evaluated using Microdilution and MTT methods, respectively. It was determined that AuNPs were effective in suppressing the proliferation of 0.02-1.00 μg/mL concentration range on Staphylococcus aureus ATCC 29213, Bacillus subtilis ATCC 11774, Escherichia coli ATCC25922, Pseudomonas aeruginosa (ATCC27833) and Candida albicans pathogenic strains. The viability of CaCo-2, Skov-3, and U118 cancer cells was effectively inhibited by the produced AuNPs by, respectively, 66.73%, 30.93%, and 23.23%. It has been determined that AuNPs have significant antimicrobial and anticancer effects on hospital pathogens and cancer cell lines.